Anti-Ro52 positivity is associated with progressive interstitial lung disease in systemic sclerosis—an exploratory study - Hamberg, Viggo; Sohrabian, Azita; Volkmann, Elizabeth R.; Wildt, Marie; Löfdahl, Anna; Wuttge, Dirk M.; Hesselstrand, Roger; Dellgren, Göran; Westergren-Thorsson, Gunilla; Rönnelid, Johan; Andréasson, Kristofer (Arthritis research & therapy, 2023)
Background Interstitial lung disease (ILD) is the most common cause of death in patients with systemic sclerosis (SSc). Prognostic biomarkers are needed to identify SSc-ILD patients at risk for progressive pulmonary fibrosis. This study investigates autoantibodies measured in bronchoalveolar lavage (BAL) fluid and in serum in reference to the clinical disease course of SSc-ILD. Methods Fifteen patients with new onset SSc-ILD underwent bronchoscopy. Autoantibody levels were analyzed using addressable laser bead immunoassay from BAL fluid and the serum. In a separate longitudinal cohort of 43 patients with early SSc-ILD, autoantibodies in serum were measured at baseline and pulmonary function tests were performed at least 2 times over the course of at least 2 or more years. Linear mixed effect models were created to investigate the relationship between specific autoantibodies and progression of SSc-ILD. Finally, lung tissue from healthy controls and from subjects with SSc was analyzed for the presence of the Ro52 antigen using immunohistochemistry. Results Among SSc-ILD patients who were positive for anti-Ro52 (N = 5), 3 (60%) had enrichment of anti-Ro52 in BAL fluid at a ratio exceeding 50x. In the longitudinal cohort, 10/43 patients (23%) were anti-Ro52 positive and 16/43 (37%) were anti-scl-70 positive. Presence of anti-Scl-70 was associated with a lower vital capacity (VC) at baseline (-12.6% predicted VC [%pVC]; 95%CI: -25.0, -0.29; p = 0.045), but was not significantly associated with loss of lung function over time (-1.07%pVC/year; 95%CI: -2.86, 0.71; p = 0.230). The presence of anti-Ro52 was significantly associated with the loss of lung function over time (-2.41%pVC/year; 95% CI: -4.28, -0.54; p = 0.013). Rate of loss of lung function increased linearly with increasing anti-Ro52 antibody levels (-0.03%pVC per arbitrary units/mL and year; 95%CI: -0.05, -0.02; p < 0.001). Immunohistochemical staining localized the Ro52 antigen to alveolar M2 macrophages in peripheral lung tissue both in subjects with and without SSc. Conclusions This study suggests that antibodies targeting Ro52 are enriched in the lungs of patients with new-onset SSc-ILD, linking Ro52 autoimmunity to the pulmonary pathology of SSc. Clinical and immunohistochemical data corroborates these findings and suggest that anti-Ro52 may serve as a potential biomarker of progressive SSc-ILD. Keywords: Systemic sclerosis, Interstitial lung disease, Ro52, Autoantibody, Biomarker